Ladies' botany or, a familiar introduction to the study of the natural system of botany - Lindley, John 1799-1865 (Cambridge University Press, 2015)
The horticulturalist John Lindley (1799-1865) worked for Sir Joseph Banks, and was later instrumental in saving the Royal Horticultural Society from financial disaster. He was a prolific author of works for gardening practitioners but also for a non-specialist readership, and many of his books have been reissued in this series. The first volume of this two-volume work was published in 1834, and the second in 1837. At a time when botany was regarded as the only science suitable for study by women and girls, Lindley felt that there was a lack of books for 'those who would become acquainted with Botany as an amusement and a relaxation', and attempted to meet this need. The first volume, in the form of engaging letters to a lady, was originally intended to stand alone. Illustrated with detailed botanical drawings, it schools the student in botanical form and taxonomy as well as nomenclature.